Retrospective evaluation of gastrointestinal system infections: Investigation of viral, bacterial, and parasitic etiological agents (Annals of Medical Research, 2022)
Aim: We aimed to retrospectively investigate the viral, bacterial, and parasitic etiological agents detected in patients to present with gastrointestinal complaints and examine their distribution in our region.Materials and Methods: Patients who presented to the XXX Hospital due to gastrointestinal symptoms between January 2017 and December 2019 were included in the study. The results obtained using conventional culture and immunochromatographic (IC) methods from the stool samples of the patients for etiological diagnosis in the microbiology laboratory were retrospectively evaluated. The infectious etiological agents were analyzed according to the age groups. Clinical and epidemiologic characteristics of the agents have been described.Results: The positivity rates were 6.6%, 2.2%, and 0.4% for Rotavirus (RV), Adenovirus (AV), and Norovirus (NV); 0.8%, 2.8%, and 0.4% for Salmonella spp., Helicobacter pylori, and Clostridium difficile; and 2.1% and 1.1% for Entamoeba histolytica and Cryptosporidium spp., respectively. Shigella spp. and Giardia intestinalis were not detected in any of the samples. The highest positivity rates in the 0–2, 3–10 and 11–20 age groups were found for RV, whereas in the 21–40, 41-60 and >60 age groups were determined for H. pylori. RV infections were observed predominantly in the spring.Conclusion: IC methods are a helpful tool for the routine diagnosis of gastrointestinal infections at hospitals. The agent with the highest positivity rate was RV. Still, the overall positivity rates were low due to the good infrastructure of our city and the successful execution of sanitation measures.
Keywords: Bacterial infection; gastrointestinal infection; immunochromatographic test; parasites